Multimedia as a didactic tool for teachers in elementary education in Croatia - Unić, Danijela; Mikelić Preradović, Nives; Posavec, Kristina (2014)
This paper presents the current situation regarding multimedia education in primary schools in Croatia. It specifically concentrates on teachers in primary schools and their mission in informatics and multimedia literacy education. The new technology and multimedia environment put forward new requirements to teachers: they are expected to become lifelong learners, but also to be informational, multimedia and IT literate. The motivation and satisfaction of elementary school teachers in Croatia related to multimedia literacy education is analyzed and revealed in this paper. Also, our comparative statistical analysis showed that there is a significant correlation between results students achieve in the multimedia literacy test and the teacher’s use of multimedia teaching materials in the classroom.
ENG